Preparation of safflower fermentation solution and study on its biological activity - Tang, Nan; Xu, Xiaoqing; Guo, Zhenyu; Meng, Xiangyu; Qian, Guoqiang; Li, He (Frontiers in Microbiology, 2024)
In this study, a fermentation solution of safflower was developed by using microbial fermentation technology. The optimal fermentation conditions were determined by single factor test and response surface method. Then the antioxidant and anti-inflammatory effects of safflower fermentation liquid were verified by cell and zebrafish models. Finally, the safety of safflower fermentation liquid was evaluated by eye irritation test of cosmetics. Results The flavonoid of safflower was increased after fermentation, which had anti-inflammatory and antioxidant properties.